The influence of the position of the medial portal and of lower leg flexion on the length of the femoral tunnel in anatomic anterior cruciate ligament reconstruction: A cadaveric study - Begović Ninoslav; Kadija Marko; Santrač-Stijak Gordana; Ille Mihajlo; Mališ Miloš; Starčević Ana; Vekić Berislav; Stijak Lazar (Vojnosanitetski Pregled)
Background/Aim. The key to successful anterior cruciate ligament reconstruction lies in the proper positioning of the femoral tunnel within the anatomical footprint and in providing for an adequate length of this tunnel without perforation to the lateral cortex. The aim of this study was to determine the change in the length of the femoral tunnel drilled during anatomic anterior cruciate ligament (ACL) reconstruction, depending on: the position of the limb being operated on, the degree of knee flexion, as well as the angle between the drill and the medial aspect of the lateral condyle. Methods. This study was performed on 16 cadaveric knees (6 male and 10 female) of the average age of 83. After the subcutaneous tissue was dissected, the femoral insertion of the ACL was identified. Then, 18 tunnels were drilled through the center of the femoral insertion with the help of 2 mm thick Kirschner wires. This was performed in two stages. In the first phase the leg was positioned on an arthroscopic leg holder, while in the second phase the leg was positioned on the table. In each phase the knee was placed in three different flexion positions (110°, 120° and 130°) and for each position three tunnels were drilled (70°, 60° and 50°) in relation to the medial aspect of the lateral condyle. Results. The average length of the femoral tunnel drilled with the leg positioned on the operating table (36.6 ± 4.7 mm) was highly statistically significantly greater (p = 0.000) in comparison with the length of the femoral tunnel obtained by positioning the leg on a fixed arthroscopic leg holder (35.4±4.3 mm). The greatest lengths of the femoral tunnel were obtain with the leg flexed at 130º and the reamer positioned at 50º angle in relation to the medial aspect of the lateral condyle (43 mm on the operating table and 41 mm on a fixed leg holder), while the shortest tunnel (33 mm on the operating table and 31 mm on a fixed leg holder) was obtained with the lower leg flexed at 110º and the reamer positioned at a 70º angle. Conclusion. The optimal position of the leg on a fixed leg holder for obtaining a femoral tunnel of sufficient length requires lower leg flexion of 120º and the position of the medial portal which enables the positioning of the reamer at a 60º angle in relation to the medial aspect of the lateral condyle. With the leg positioned on the operating table, it becomes unnecessary to push the leg into flexion greater than 110º; rather a longer femoral tunnel is achieved by lateralization of the medial portal.